Safety of DNA and modified vaccinia virus Ankara vaccines against liver-stage P. falciparum malaria in non-immune volunteers - Moorthy, V; McConkey, S; Roberts, M; Gothard, P; Arulanantham, N; Degano, P; Schneider, J; Hannan, C; Roy, M; Gilbert, S; Peto, T; Hill, A (2003)
A series of phase I clinical studies were conducted to evaluate the safety of plasmid DNA and modified vaccinia virus Ankara malaria vaccines. The vaccines each encoded a polyepitope string fused to whole Plasmodium falciparum TRAP antigen. Forty-three healthy adult volunteers received the vaccines alone or in DNA/MVA prime-boost combinations. The DNA vaccine was administered either intramuscularly by needle or intradermally by a needleless delivery device. The MVA vaccine was administered intradermally by needle. The vaccines were well-tolerated by all three routes and in various DNA/MVA immunisation regimes. There were no severe or serious adverse events. © 2002 Elsevier Science Ltd. All rights reserved.